2011
DOI: 10.1002/anie.201006065
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of β‐Agostic Bonding in Late‐Transition‐Metal Alkyl Complexes

Abstract: In general, C À H bonds can be considered chemically inert as a result of their strength, nonpolar nature, and low polarizability. Since the pioneering work of La Placa and Ibers in 1965, who reported the close approach of a CÀH bond to a transition-metal center, there have been many attempts to trace the microscopic control parameters of such C À H activation processes by metal atoms in general.[1] In particular, complexes containing side-on-coordinated (h 2 -CH) moieties next to a transition metal are the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 32 publications
3
76
0
Order By: Relevance
“…. [84][85][86][87] In these contacts an existence of the interaction is manifested by decrease in 1 J(C-H) coupling constants due to the interaction of C-H bond with adjacent moiety (metal, lone pair, or, like in our case, another C-H bond). Such interactions result in weakening of C-H bonds (either due to charge depletion from occupied (C-H) orbital or due to population of the empty *(C-H)).…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…. [84][85][86][87] In these contacts an existence of the interaction is manifested by decrease in 1 J(C-H) coupling constants due to the interaction of C-H bond with adjacent moiety (metal, lone pair, or, like in our case, another C-H bond). Such interactions result in weakening of C-H bonds (either due to charge depletion from occupied (C-H) orbital or due to population of the empty *(C-H)).…”
mentioning
confidence: 77%
“…Such interactions result in weakening of C-H bonds (either due to charge depletion from occupied (C-H) orbital or due to population of the empty *(C-H)). [84][85][86][87] It can clearly be seen from Table S14 Stabilizing contribution of these diatomic intramolecular interactions toward the overall electronic energy of complexes increases from ZnL to ZnL 3 , but an opposite trend is observed for both coordination bonds (as found from QTAIM, IQA, NCI, and ETS-NOCV).…”
mentioning
confidence: 90%
“…Accordingly, the electron density accumulation at the M···H' ago bond critical point (BCP) in 2 is rather small (1(r) exp = 0.082(4); 1(r) calc = [0.10] e À3 ) and a BCP is even lacking in case of 4. [18] The weakness of the agostic interaction in 2 also becomes obvious by direct comparison with the d 8 -Ni complex [(DCpH)Ni(d t bpe)] + [BF 4 ] À (6, DCpH = dicyclopentenyl), [19] which is our benchmark system for compounds displaying strong agostic interactions (Figure 4 b): in that case the Ni···H BCP is well pronounced (1(r) = 0.553(4) e À3 ), the NiÀH' ago bond distance (1.671 (9) ) is significantly shorter than in 2 (2.376 ), and the C À H activation is large (r(C À H) = 1.20(1) ). [19] Apparently, complexes 2, 4, and 6 represent benchmark systems for three different scenarios of agostic interactions (Figure 4).…”
Section: Methodsmentioning
confidence: 99%
“…[19] Apparently, complexes 2, 4, and 6 represent benchmark systems for three different scenarios of agostic interations (Figure 4). In the final step of our analysis we will focus on the NMR properties of 1 and 2 which display in 1 H NMR experiments rather different chemical shifts of the agostic protons (Scheme 2).The agostic protons in 1 are clearly shifted upfield ( ( 1 H) = -5.88 ppm) but downfield in 2 ( ( 1 H) = +6.1 ppm).…”
Section: Orbitals In M•••h-c Interactions"mentioning
confidence: 99%
“…For late transition‐metal complexes, Scherer et al. showed that β‐agostic interactions can be described in terms of the Dewar–Chatt–Duncanson model, which involves π donation and backdonation between the metal atom and the alkyl backbone …”
Section: Introductionmentioning
confidence: 99%